Analisis Gaya Bahasa Dalam Pidato Nadiem Makarim Rekomendasi Sebagai Modul Ajar Tingkat SMP Kelas VIII (Kajian Stilistika) - Anisya Mutiara Oktavia; Ferina Meliasanti; Daman Huri (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Speaking skills instruction in Indonesian language classes at the junior high school level, particularly in speech text materials, still tends to emphasize the understanding of text structure. Meanwhile, language style as an essential element that determines the aesthetic quality, clarity, and strength of a speech message has not been optimally addressed. In fact, the appropriate use of language style can help speakers convey ideas in a more engaging and persuasive manner. Based on this context, this study aims to examine the types of language styles found in Nadiem Makarim’s speeches and to use the findings as a recommendation for a speech text learning module for eighth-grade junior high school students. This research employs a qualitative approach with a descriptive method. The data sources consist of four speech texts by Nadiem Makarim obtained from the official YouTube channel of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. Data were collected through documentation and note-taking techniques, while data analysis was conducted using a stylistic approach based on Gorys Keraf’s theory of language style. The results indicate that Nadiem Makarim’s speeches contain various types of language styles, including those based on word choice, tone, sentence structure, and both direct and indirect meanings. These language styles function to clarify ideas, build emotional closeness with the audience, and strengthen the persuasive power of the speech. The findings of this study were then developed into a recommended learning module aligned with the Merdeka Curriculum, which is expected to enrich teaching materials and improve the speaking skills of eighth-grade junior high school students.